Scientific Horizon: Basis for Developing Basic Mathematics Teaching Materials - Kusaeri, Al; Pardi, Habib Husnial; Evendi, Erpin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study explores the development and validation of mathematics teaching materials that integrate Islamic values to foster both cognitive and ethical growth in students. Utilizing the scientific horizon model, these materials were designed to connect mathematical concepts with Islamic teachings, making learning relevant to students’ cultural and spiritual backgrounds. The development followed the Plomp model, with five stages: initial investigation, design, development, evaluation, and dissemination. Expert validation rated the materials as "valid" (average score of 4.09), affirming their educational rigor and cultural appropriateness. Field trials with 50 first-semester students from the Mathematics Education Study Program at the State Islamic University of Mataram showed high student engagement, with over 90% expressing positive responses. Students reported that the contextualized lessons—such as using modular arithmetic to calculate prayer cycles and exploring infinity through Qur’anic reflections—enhanced their understanding and engagement. This study demonstrates that integrating Islamic values into mathematics not only aids in comprehension but also promotes ethical reflection, supporting the holistic educational mission of Islamic institutions. Recommendations for future research include broader implementation across educational contexts and expansion into other STEM subjects.